The institutional framework of ethnic inclusion and exclusion: A cross-national analysis of the earnings of foreigners in Germany and immigrants in Canada - Jeffrey G. Reitz; Joachim R. Frick; Tony Calabrese; Gert G. Wagner (Deutsches Institut für Wirtschaftsforschung (DIW), 1998)
The European social-welfare model differs from the North American individualistic model in the patterns, more than the overall extent, of ethnic inclusion and exclusion. Focussing on foreigners in Germany and immigrants in Canada as illustrative cases, conventional earnings decomposition analysis is extended cross-nationally to highlight institutional effects, using the German Socio-Economic Panel (GSOEP) first wave for 1984, and the 1986 Canadian Census. German education and labor market institutions benefit low-skill migrants, but generate less earnings assimilation. Such assimilation in Canada is greater but varies more by ethnic and racial origins. Institutional frameworks may generate social imperatives shaping patterns of ethnic inclusion and exclusion, quite apart from national policies of citizenship or culture.
Keywords: 330; Internationale Wanderung; Soziale Integration; Einkommen; Lohn; Ethnische Gruppe; Vergleich; Deutschland; Kanada